2023
DOI: 10.3390/ijerph20021367
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Stressors and Clinical Mental Health Symptoms in a Northeast US Sample

Abstract: Research has linked specific COVID-19-related stressors to the mental health burden, yet most previous studies have examined only a limited number of stressors and have paid little attention to their clinical significance. This study tested the hypothesis that individuals who reported greater COVID-19-related stressors would be more likely to have elevated levels of anxiety, posttraumatic stress symptoms, and serious psychological distress. Methods: An online survey was administered to a convenience sample fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…This global public health crisis created disruption across a range of important life domains, leading to personal, societal, health-related, employment-related, and financial stressors [ 45 ]. Consistent with this proposition, a review of studies conducted during the early period of the pandemic found that procrastination increased in a number of different contexts, notably in academic settings [ 59 ]. For example, one study conducted during the COVID-19 pandemic with a sample of almost 9000 university students found that higher perceived stress increased students’ procrastination [ 60 ].…”
Section: Covid-19 Stress and Vulnerability For Procrastinationmentioning
confidence: 89%
See 1 more Smart Citation
“…This global public health crisis created disruption across a range of important life domains, leading to personal, societal, health-related, employment-related, and financial stressors [ 45 ]. Consistent with this proposition, a review of studies conducted during the early period of the pandemic found that procrastination increased in a number of different contexts, notably in academic settings [ 59 ]. For example, one study conducted during the COVID-19 pandemic with a sample of almost 9000 university students found that higher perceived stress increased students’ procrastination [ 60 ].…”
Section: Covid-19 Stress and Vulnerability For Procrastinationmentioning
confidence: 89%
“…As shown in Figure 2 , there were four key sources of stress during the COVID-19 pandemic. In addition to the looming health threats associated with the pandemic, and adjusting to new regulations for how to stay safe in public, many individuals experienced stress due to changes in their working routines, a decrease in their level of social interactions, changes in the delivery of academic work, and even threats to their financial security as a result of the pandemic [ 59 , 62 , 63 ]. For some individuals, the stress due to fears about becoming infected and from the socio-economic impacts of the pandemic became so extreme that some clinicians suggested that it reflected a new COVID stress syndrome [ 64 ].…”
Section: Covid-19 Stress and Vulnerability For Procrastinationmentioning
confidence: 99%
“…Consequently, art students may experience heightened worries and uneasiness about the culture examination and art examination, which to some extent affects their test anxiety levels. On the other hand, the stress caused by COVID-19 may make individuals feel nervous and anxious [4]. Art students have higher stress levels and poorer mental health than non-art students [10].…”
Section: The Influence Of Covid-19 Stress On Test Anxietymentioning
confidence: 99%
“…COVID-19 has emerged as a significant health threat, posing a vital threat to the mental and physical wellbeing of individuals worldwide [1][2][3]. COVID-19 stress can lead to various physical and psychological problems in individuals such as depression, anxiety, poor sleep quality, and other problems [4,5]. For the students, the negative effects of COVID-19 stress are mainly related to academic stress and anxiety [6].…”
Section: Introductionmentioning
confidence: 99%
“…La intolerancia a la incertidumbre y la exposición a los medios de comunicación son poderosos predictores del impacto (Sandín et al, 2020). Monnig et al (2023) han estudiado individuos que tenían 18 años o más en los cinco estados del nordeste de los Estados Unidos más afectadas por infecciones y muertes por COVID 19. La investigación ha relacionado factores estresantes específicos de la infección por Sars-coV-2 con la carga de salud mental.…”
Section: Tonon Da Luz Et Alunclassified